Phase Transformation of CuInxGa1-x-Se2 Powder by Milling and Heat Treatment - Gu, Sin-Il; Shin, Hyo-Soon; Yeo, Dong-Hun; Nahm, Sahn (Asian Journal of Chemistry, 2012)
CuInxGa1-x-Se2 ink and paste by milling and subsequent heat treatment to remove organic compounds contained in the thick film are to be crucial to produce dense CuInxGa1-x-Se2 absorber layer, however, few studies has been performed to address such processes. The object of this study is to identify wet milling conditions for CuInxGa1-x-Se2 powder and observe its phase transition and pertinent morphology change according to different heat treatments of CuInxGa1-x-Se2. CuInxGa1-x-Se2 powder was dispersed in planetary mill containing diethylamine as solvent and exhibited no phase transformation. CuInxGa1-x-Se2 disappeared after annealed in air at 200 ºC or more. In the case of Se-N2-H2 atmosphere, secondary phase in small portion was formed after annealed at 150 ºC up to 300 ºC whereas CuInxGa1-x-Se2 was maintained above it. Dense CuInxGa1-x-Se2 film was obtained after sintered in Se-H2-N2 at 800 ºC.